EFFECTIVENESS OF INORGANIC WASTE MANAGEMENT IN SIGLI DISTRICT : Study of Pidie Regency Regulation No. 6 of 2012 on Waste Management - Pratama, M. Ariq Riju; Siddiq Armia, Muhammad; Abdullah, Arifin (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2026)
This study analyzes the effectiveness of inorganic waste management in Sigli District based on the implementation of Pidie Regency Regulation No. 6 of 2012. A descriptive qualitative research method was applied with data collection through in-depth interviews with the Environmental Agency and the community, as well as a review of relevant literature. The results of the study show that the implementation of waste management policies is still not optimal. Various obstacles hinder its effectiveness, particularly limitations in infrastructure such as the number of transport vehicles and TPS/TPA facilities, low human resource capacity, and community behavior that does not support the existing management system. In addition, inadequate road infrastructure also slows down the transportation process. This study concludes that improvement efforts are needed through the strengthening of supporting regulations, increased budget allocation, community empowerment, and coordination among stakeholders. These recommendations are expected to improve the effectiveness of inorganic waste management towards a more sustainable system that is in line with local conditions in the Sigli District.